Investigation of aerosols pollution across the eastern basin of Urmia lake using satellite remote sensing data and HYSPLIT model - Delfi, Shokufeh (J Environ Health Sci Eng, 2019)
BACKGROUND: Desiccation of the world’s second hypersaline lake, Lake Urmia, has drawn attention toward the feasibility of particle emissions from the lakebed to downwind regions. Therefore, this research was conducted to study spatiotemporal variations of aerosols across the eastern basin of the lake during 2001 to 2016. METHODS: The Aerosol Optical Depth (AOD) products of Moderate-resolution Imaging Spectroradiometer (MODIS), extracted from Terra platform for 999 rural and urban areas and compared over adjacent (Shabestar, Osku, Azarshahr, Ajabshir, Bonab, Malekan), middle (Tabriz and Maragheh) and far (Bostanabad, Heris, and Sarab) counties. Number of dusty days and direction of high wind speeds (≥ 11 m/s) were acquired from the East Azerbaijan Meteorological Organization and analyzed. Moreover, performing the backward trajectory model, the origin and distribution of aerosols were determined at altitudes of 500, 1000 and 2000 m. RESULTS: The spatiotemporal variations of AOD provided statistically significant correlations (R(2) ≥ 0.5 and p < 0.05) against the number of dusty days. AOD value was higher between 2009 and 2016 and estimated to be 0.36, 0.33 and 0.31 over adjacent, middle and far areas, respectively. Analysis of wind direction and trajectory plots implied that the particulate matter (PM) of study area was mainly transported from Iraq and Syria, especially in April, May and June months. CONCLUSIONS: PM has followed an increasing trend, while the adjacent areas have experienced higher pollution compared to far counties. The southwestern winds can play an important role in transportation of aerosols from either lakebed or western countries to the study area.